The effect of green growth strategy on corporate sustainability performance - AshaAri M.J.; Daud S. (American Scientific Publishers, 2023)
Imbalance of the environmental systems and economy activities are putting development and economic growth at risks and thus Malaysian government is focusing on corporate sustainability in the country. In achieving sustainability, Malaysian organizations have to play their role in handling the challenges of sustainability issues. This study will explore the green growth strategy features which discuss on the keys to sustain the strategy, marketing emphasis, production emphasis, product line, basis of competitive advantage and strategic target. The objective of this paper is to propose a conceptual framework on the relationship between green growth strategy and corporate sustainability performance. Future study is proposed to conduct an empirical analysis of green growth strategy on corporate sustainability performance. 2017 American Scientific Publishers. All rights reserved.